The contribution of reading comprehension skills and learning motivation to junior high school students’ news writing skills - Dina Adila; Afnita Afnita; Syahrul Ramadhan; Amril Amir (Universitas Ahmad Dahlan, 2026)
This study aims to describe and measure the extent to which reading comprehension skills and learning motivation contribute to news writing skills. This study employs a quantitative approach with a correlational design. The study population consisted of 136 seventh-grade students at SMP Negeri 30 Batang Hari, Jambi Province. A sample of 82 respondents was selected using proportionate random sampling. The data collection instruments consisted of an objective test to measure reading comprehension, a Likert scale questionnaire for learning motivation, and a performance test to assess news text writing skills. The data were statistically analyzed using the Pearson Product Moment correlation test, partial and multiple linear regression, the t-test, and the F-test. The results of the analysis confirmed the following three points. First, reading comprehension skills significantly contribute to news text writing skills by 56.10%. Second, learning motivation contributes significantly by 40.45%. Third, reading comprehension skills and learning motivation simultaneously contribute 56.25% to news text writing skills. Based on these research results, it is concluded that mastery of text comprehension and the level of learning motivation are key predictors of the quality of students’ news articles. Improving students’ ability to produce functional texts requires schools to integrate analytical reading exercises with the cultivation of a supportive learning environment in the classroom.